Rearrangement of the beta chain of the T cell antigen receptor and immunoglobulin genes in lymphoproliferative disorders. - Griesser, H (1986)
55 samples representing Hodgkin's and non-Hodgkin's lymphoma and other hyperplastic lesions of the lymph node were examined for rearrangement of the beta chain of the T cell antigen receptor (TcR) and Ig genes. In non-Hodgkin's lymphoma, rearrangement of TcR beta was found in all 14 T cell lymphomas and in two of the seven B cell lymphomas. Ig gene rearrangement was found in none of the 14 T cell lymphomas and in all seven B cell lymphomas. We also examined DNA from lymph nodes in which the lineage of the malignant cell is not clear. Rearrangement of TcR beta was found in all five lymphoepitheloid cell (Lennert's) lymphomas; four of eight Hodgkin's lymphomas; seven of ten Ki 1+ lymphomas; and all nine cases of angioimmunoblastic lymphoadenopathy (AIL). Ig gene rearrangement was found in none of five lymphoepitheloid cell lymphomas; none of eight Hodgkin's lymphomas; three of ten Ki 1+ lymphomas; and four of nine cases of AIL. These findings indicate that genetic studies of TcR and Ig genes are useful in identifying the presence of a clonal population in a lymph node, in determining the extent of the clonal population, and aid in identifying lineage. Of special interest was the finding that some cases of Hodgkin's lymphoma and AIL contain clonal rearrangement of the TcR genes, which suggests that in those cases the malignant cells may be of T cell origin.